Education in Lithuania (Reviews of National Policies for Education, 2017)
Lithuania has achieved steady expansion of participation in education, substantially widening access to early childhood education and care and tertiary education, coupling this with nearly universal participation in secondary education. However, if Lithuania’s education system is to help the nation respond effectively to economic opportunities and demographic challenges, improvements in the performance of its schools and its higher education institutions are needed. Improved performance requires that Lithuania clarify and raise expectations of performance, align resources in support of raised performance expectations, strengthen performance monitoring and the assurance of quality, and build institutional capacity to achieve high performance. This orientation to improvement should be carried across each sector of its education system. This report assesses Lithuania’s policies and practices against best practice in education from across the OECD and other countries in the region. It analyses its education system’s major strengths and the challenges it faces, from early childhood education and care to tertiary education. It offers recommendations on how Lithuania can improve quality and equity to support strong, sustainable and inclusive growth. This report will be of interest in Lithuania and other countries looking to raise the quality, equity and efficiency of their education systems